Congress Second Report of the Economic, Social and Political Committee - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): International Federation of Free Trade Unions The Congress commends heartily the UN Special Committee for its searching, comprehensive and enlightening report on the Soviet Government's suppression of the Hungarian democratic revolution.